2015
DOI: 10.1007/s10384-015-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with myopia in primary school students in the Chaoyang District of Beijing, China

Abstract: The prevalence of myopia among primary school children in Beijing increased with age, and was significantly higher in girls ≥10 years old. Myopia was significantly associated with parental myopia, reading posture, distance between the eyes and the book being read, font size used in extracurricular reading material, time spent studying at home, and the duration of continuous study time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…We also found that the prevalence of myopia in girls was higher than that in boys, which was consistent with the findings in other Chinese locations, such as Guangzhou [15] and Xichang [24]. Previous studies indicated that older children had a higher risk of myopia [2,15,25], which was further confirmed by our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that the prevalence of myopia in girls was higher than that in boys, which was consistent with the findings in other Chinese locations, such as Guangzhou [15] and Xichang [24]. Previous studies indicated that older children had a higher risk of myopia [2,15,25], which was further confirmed by our study.…”
Section: Discussionsupporting
confidence: 92%
“…Myopia, which threatens visual quality and eye health, is a common refractive error among children and teenagers worldwide. Notably, the myopia prevalence is particularly high in east Asian countries; the prevalence in children 6-12 years of age is 53.9% in Tianjin, China [1], 36.7% in children aged 5-14 years in Beijing [2], 69.5% in teenage children in Singapore [3], 24.8% in 12-yearsolds in Malaysia [4], 22.6% in Korean children [5]. Studies have suggested that both genetic and environmental factors have a marked impact on myopia in school children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study, based on cycloplegic autorefraction, found that the overall prevalence of myopia was 59.2% among 6‐ to 14‐year‐old school children in urban Tianjin, China. Similarly, Lyu et al . reported that myopia was present in 36.7% of 4249 students aged 5–14 years in Beijing in 2015.…”
Section: Discussionmentioning
confidence: 90%
“…Lyu et al [4] investigated the reading habits, visual behaviors and living environments of elementary school children in Chaoyang District, Beijing and found that myopia was associated with reading posture, reading distance, and font size. You et al [19] note that dim illumination during reading is an additional factor in the development of myopia.…”
Section: Reading Habits and Visual Health Behaviorsmentioning
confidence: 99%